Dependence on Autophagy for Autoreactive Memory B Cells in the Development of Pristane-Induced Lupus - Jang, Albert; Sharp, Robert; Wang, Jeffrey M.; Feng, Yin; Wang, Jin; Chen, Min (Frontiers in Immunology, 2021)
The production of autoantibodies by autoreactive B cells plays a major role in the pathogenesis of lupus. Increases in memory B cells have been observed in human lupus patients and autoimmune lpr mice. Autophagy is required for the maintenance of memory B cells against viral infections, however, whether autophagy regulates the persistence of autoantigen-specific memory B cells and the development of lupus remains to be determined. Here we show that memory B cells specific for autoantigens can be detected in autoimmune lpr mice and a pristane-induced lupus mouse model. Interestingly, B cell-specific deletion of Atg7 led to significant loss of autoreactive memory B cells and reduced autoantibody production in pristane-treated mice. Autophagy deficiency also attenuated the development of autoimmune glomerulonephritis and pulmonary inflammation after pristane treatment. Adoptive transfer of wild type autoreactive memory B cells restored autoantibody production in Atg7-deficient recipients. These data suggest that autophagy is important for the persistence of autoreactive memory B cells in mediating autoantibody responses. Our results suggest that autophagy could be targeted to suppress autoreactive memory B cells and ameliorate humoral autoimmunity.